Additive manufacturing of heat-resistant aluminum alloys: a review - Wu, Chaoqun; Wen, Jianyu; Zhang, Jinliang; Song, Bo; Shi, Yusheng (International Journal of Extreme Manufacturing, 2024)
The capability for synergistic advancements in both making and shaping afforded by additive manufacturing (AM) enables the flexible production of high-performance components. Boosted by the growing demand for heat-resistant aluminum alloys in the moderate-temperature weight-critical applications, AM of heat-resistant aluminum alloys constitutes a burgeoning field. Although numerous advances have emerged in recent years, there remains a gap in the review literature elucidating the newly-developed alloy systems and critically evaluating the efficacy. This state-of-the-art review presents a detailed overview of recent achievements on the heat-resistant aluminum alloy development. It begins with the introduction of various AM technologies and the pros and cons of each technique are evaluated. The enhancement mechanisms associated with printability and high-temperature properties of AM aluminum alloys are then delineated. Thereafter, the various additively manufactured aluminum alloy systems are discussed with regard to the microstructure, heat resistance and high-temperature performance. An emphasis is put on the powder bed fusion-laser beam (PBF-LB) as it has garnered significant attention for heat-resistant aluminum alloys and the vast majority of the current studies are based on this technique. Finally, perspectives are outlined to provide guidance for future research. AM technologies for metals are evaluated with an emphasis on PBF-LB technique. Eutectic systems and inoculation treatment enable crack suppression of AM Al alloys. The high-temperature strengthening mechanisms of AM Al alloys are discussed. Microstructures and heat resistance of various AM Al alloy systems are evaluated. Perspectives on AM heat-resistant Al alloys are outlined.